The resilience of nurses in caring for children who experience terminality - Bruna Raiane Viana Andrade; Juliana Xavier Pinheiro da Cunha; Chrisne Santana Biondo (Universidade Federal de Santa Maria, 2020)
Objective: to investigate the resilience of nurses in caring for children experiencing terminality in intensive care. Method: a qualitative study conducted with 12 Pediatric and Neonatal Intensive Care Unit nurses of two hospitals in the countryside of Bahia. Data collection occurred in April and May 2019, and semi-structured interview was used, analyzed through Collective Subject Discourse. Results: it was evidenced the difficulty of nurses in dealing with child terminality, referring to anguish and impotence, more intensely to those who are mothers. Empathy and spirituality proved to be important in caring for terminally ill children and in developing resilience. Conclusion: it is necessary that finitude be faced as a natural course of life. Thus, studies on the theme should be expanded and educational and labor institutions invest in discussions about terminality so that nurses develop coping mechanisms and build resilience in child care.